Linguistic Analysis of English and Uzbek Economical Lexical Units - Avazova Zebuniso Salayevna (Scientific Trends, 2025)
The article examines the topicality of studying English and Uzbek proverbs, idioms on economy. We studied proverbs through a comparative analysis of both languages in order to distinguish economic concepts, which play an important role in people's daily life and society. In addition, special attention is paid to the main aspects of the use of idioms, meaning "economy," which may reflect the linguistic richness and cultural paradigms of the speakers of a particular language.
Keywords: Economic terms, formation, Uzbek and English languages, suffixes.